1994
DOI: 10.1210/jcem.78.2.7906280
|View full text |Cite
|
Sign up to set email alerts
|

Glucoregulation during and after intense exercise: effects of beta-blockade.

Abstract: To define the roles of beta- and alpha-adrenergic receptors in intense exercise, 17 lean healthy fit young males underwent 13.6 +/- 0.2 (+/-SE) min of cycle ergometer exercise: 6 at 100% maximum oxygen uptake (VO2max; MAX), 7 at their maximum possible (87 +/- 2.3%) during iv propranolol (P; 150 micrograms/kg bolus 30 min preexercise, then 80 micrograms/kg.min), and 7 (including 3 of the P subjects) at 87% VO2max (C) as controls for P. Plasma glucose increased from similar resting values to a peak in the early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…Frogs on the other hand, appear to follow a more 'mammalian' pattern, of significant increases in blood glucose in response to activity (Fig.·4B), coinciding with and presumably due to catecholamine release (Fournier et al, 1994). Mammals restore normoglycemia within 1·h of epinephrine clearance (Sigal et al, 1994), whereas significant hyperglycemia was persistent over the 4·h of recovery in this study (Fig.·3C) and that of Fournier et al (Fournier et al, 1994).…”
Section: Characterization Of Metabolic Recovery From Activity: Summersupporting
confidence: 58%
“…Frogs on the other hand, appear to follow a more 'mammalian' pattern, of significant increases in blood glucose in response to activity (Fig.·4B), coinciding with and presumably due to catecholamine release (Fournier et al, 1994). Mammals restore normoglycemia within 1·h of epinephrine clearance (Sigal et al, 1994), whereas significant hyperglycemia was persistent over the 4·h of recovery in this study (Fig.·3C) and that of Fournier et al (Fournier et al, 1994).…”
Section: Characterization Of Metabolic Recovery From Activity: Summersupporting
confidence: 58%
“…On the basis of these three studies, we have suggested that during intense exercise both ␣-and ␤-receptor effects of catecholamines can increase GP (35,36,40). Because with blockade of either of the receptors the plasma concentrations of catecholamines rose considerably more, this suggests that one system can compensate for the attenuated activity of the other, i.e., there is redundancy in the receptor mechanisms in this specific situation.…”
Section: Responses (F-f) Greater Hyperglycemia With Propranolol (A) mentioning
confidence: 99%
“…5) or propranolol (Fig. 6) intravenously, starting 30 min before the bout and ending at 60 min of recovery (35,36). With phentolamine (36), the importance of the usual islet ␣-receptor effect of inhibiting insulin secretion during exercise (2,3) is clearly illustrated by the threefold increase in insulin (Fig.…”
Section: Eb Marliss and M Vranicmentioning
confidence: 99%
“…Attempts to directly assess a role for catecholamines in stimulating endogenous glucose production during high-intensity exercise (Ͼ80% maximum O 2 uptake) in humans have also been negative (43,49,59,82,83). This is not to say that other factors such as IL-6 (23) or an as yet undefined regulator do not play some role.…”
Section: Studies On the Control Of Glucose Mobilization From The Livermentioning
confidence: 99%